Hypertension and occupational stress among high school teachers of Dibrugarh district - Chetia, Dipankar; Gogoi, Gourangie; Baruah, Rupali (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is an important public health problem. High blood pressure is one of the leading risk factors for premature deaths. Job strain can impact blood pressure directly through neuro-endocrine mechanisms. Teaching in school especially at the secondary school level has been identified as one of the most stressful professions. The present study was conducted to estimate the prevalence of hypertension and its association with occupational stress among high school teachers of Dibrugarh district. Methods: A community based cross sectional study among all government high school teachers of Dibrugarh district was done. All high school teachers in the age group ≥21 years to <60 years of both sexes were included. The sample size was calculated to be 335 using the formula, n=4pq/d2. Results: Out of the 335 study participants, 45.4% were hypertensive while the remaining 54.6% were non-hypertensive. Study participants who had stress as a problem had highest prevalence of hypertension (84.6%). The association between prevalence of hypertension and occupational stress of the study participants was observed to be statistically significant as (p<0.05). Conclusions: From the findings of the study it was concluded that the prevalence of hypertension among high school teachers of Dibrugarh district was high (45.4%). The prevalence of hypertension was found to be significantly associated with occupational stress.